NTRM (Non Tobacco Related Material) TEMBAKAU RAJANGAN MADURA YANG DIUSAHAKAN PETANI MITRA P.T. SADHANA ARIFNUSA DI KABUPATEN PAMEKASAN - Hosaini, Moh; Tirtosastro, Samsuri; Sasongko, Pramono (Fakultas Pertanian, 2019)
Cigarette smoke is currently the talk of the National and international community has a positive or negative value. One of the causes of the negative impact is the increase in non-tobacco (non-tobacco related material) which is another material other than tobacco which has a great opportunity to become a source of hazardous materials, in addition to disrupting the production and aesthetic processes. This study aims to determine the content of NTRM in tobacco prepared by farmers to be sold to the warehouse of tobacco purchases in P.T. Sadhana Arifnusa, Pamekasan Regency in 2017. Sampling in this study uses a non-probability sampling technique. Respondent farmers were selected who met the criteria for planting and processing their own tobacco leaves and then sold them to the warehouse. Farmers plant and process tobacco leaves themselves into madura chopped tobacco. Farmers selected were from Bulay Village (Galis District), Guluk-guluk Village (Guluk-guluk Sub-district), Kalompang Berek Village (Pakong District), Bicorong Village (Pakong District), each in Pamekasan District. The results of the research in the Four Villages show that there is a high NTRM content. Organic NTRM and Non-Synthetic NTRM are 0.39 grams, 1.89 grams, respectively. The highest NTRM is. Organic NTRM is higher in the Guluk-guluk Village of 0.83 grams, which is higher in the Bulay Village of 3.47 grams, which is in the form of stones. The high content of NTRM in Madura chopped tobacco requires attention in the development of partner farmers especially from the local government. Salah satu penyebab dampak negatif adalah meningkatnya NTRM (Non TobaccoRelated Material) yang merupakan bahan lain selain tembakau yang berpeluang besar ikut menjadi sumber bahan berbahaya, selain mengganggu proses produksi dan estetika. Penelitian ini bertujuan menentukan kandungan NTRM pada tembakau yang disiapkan petani untuk dijual ke gudang pembelian tembakau di gudang P.T. Sadhana Arifnusa Kabupaten Pamekasan pada tahun 2017. Pengambilan sampel dalam penelitian ini menggunakan metode non-probability sampling technique. Petani responden dipilih yang memenuhi kriteria menanam dan mengolah daun tembakaunya sendiri kemudian akan dijual ke gudang. Petani menanam dan mengolah sendiri daun tembakau menjadi tembakau rajangan madura. Petani yang dipilih berasal dari Desa Bulay (Kecamatan Galis), Desa Guluk-Guluk (kecamatan Guluk-Guluk), Desa Kalompang Berek (Kecamatan Pakong), Desa Bicorong (Kecamatan Pakong), masing-masing di Kabupaten Pamekasan. Hasil penelitian di Empat Desa tersebut menunjukkan ada kandungan NTRM yang cukup tinggi. NTRM Organik dan NTRM Non Sintetik masing-masing 0,39 gram, 1,89 gram. NTRM paling tinggi adalah. NTRM Organik lebih tinggi di Desa Guluk-Guluk sebesar 0,83 gram, yang berupa batang tanaman, daun dan NTRM Non Sintetik lebih tinggi di Desa Bulay sebesar 3,47 gram, yang berupa batu. Tingginya kandungan NTRM tembakau rajangan madura, memerlukan perhatian dalam pembinaan kepada Petani Mitra khususnya dari Pemerintah Daerah.